Digital health in Indonesia: A literature review of adoption, infrastructure, equity, and health-system transformation - Olivia Putri Dahlan (Health Economics Insights Journal, 2026)
Digital health has moved from a peripheral innovation agenda to a central health-system transformation agenda in Indonesia. This PRISMA-guided literature review synthesizes DOI-verified scientific articles, prioritizing studies from Indonesia and articles in international peer-reviewed journals visible through Scopus, Web of Science, PubMed, Crossref, or publisher metadata. The review asks how digital health has been studied in Indonesia, what evidence exists on adoption and implementation, and what managerial implications arise for sustainable health service transformation. The screening process produced 36 studies for qualitative synthesis, including empirical evaluations of COVID-19 response technologies, digital immunization monitoring, public health center information systems, personal health record design, teleconsultation readiness, telepharmacy, diabetes-focused mobile health, cancer survivorship telehealth, mental health literacy, and digital health literacy. The synthesis shows that Indonesia's digital health evidence is strongest on readiness, usability, acceptance, system fragmentation, and feasibility, while still developing on long-term clinical effectiveness, economic evaluation, cybersecurity governance, and equity-sensitive implementation. Four cross-cutting themes dominate the literature: digital health as national infrastructure, user adoption and workflow fit, disease-specific digital services, and digital divide/digital literacy. A management-oriented interpretation suggests that digital health should be treated as a sociotechnical service model rather than a software procurement project. Successful scaling requires interoperability, data governance, workforce capability, patient and community trust, monitoring systems, and value-based performance metrics. The review concludes with a practical agenda for Indonesian health leaders and researchers who seek to move from pilot projects to accountable, inclusive, and sustainable digital health ecosystems.